Minerals In The World Economy - Summary Of International Events Impacting The Minerals Economy In 1993 - Michael D. Fenton (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Social and political movements that had been gathering momentum over several years continued in 1993 to dramatically affect and inspire uncertainty on the global mineral industry. Privatization of government-controlled mineral industries continued throughout the world, especially in Africa, Asia, Central Eurasia, Eastern Europe, Latin America, and Western Europe. The reasons for privatization varied among regions and countries, but the trend was universal and was not expected to end soon. Regional trade blocks were being developed and expanded. The European Union (EU), the North American Free Trade Area (NAFTA), the Association of Southeast Asian Nations (ASEAN) , the Asia Pacific Economic Cooperation (APEC) , and the Latin American Southern Cone Common Market (MERCOSUR) were expected to contribute to reduced internal tariffs and increased minerals trade. Minerals consumption within the politically unstable former Soviet Union (FSU) decreased significantly without a simultaneous cutback in production, while its exports flooded the world's mineral markets. These exports into Western Europe and Japan, still in economic recession, depressed minerals and metals prices worldwide, especially for aluminum, magnesium, nickel, and potash. Increasingly restrictive environmental laws and land-access limitations in Australia, Canada, Western Europe, and the United States tended to discourage mineral resource development. However, the number of undeveloped countries in Latin America and Asia that encouraged exploration and development by revising mining and tax laws and regulations increased, thereby increasing investment opportunities for foreigners.